Voice, Speech, and Laryngeal Features of Primary Sjögren's Syndrome. (November 2014) - Heller, Amanda; Tanner, Kristine; Roy, Nelson; Nissen, Shawn L.; Merrill, Ray M.; Miller, Karla L.; Houtz, Daniel R.; Ellerston, Julia; Kendall, Katherine
Objective: This study examined voice, speech, and laryngeal characteristics in primary Sjögren's syndrome (pSS). Methods: Eleven patients (10 female, 1 male; mean [SD] age = 57 [14] years) from The University of Utah Division of Rheumatology provided connected speech and sustained vowel samples. Analyses included the Multi-Dimensional Voice Profile, the Analysis of Dysphonia in Speech and Voice, and dysphonia severity, speech clarity, and videolaryngostroboscopy ratings. Results: Shimmer, amplitude perturbation quotient, and average fundamental frequency differed significantly from normative values ( P < .01). Cepstral Spectral Index of Dysphonia values indicated mild-to-moderate dysphonia in connected speech (mean [SD] = 20.26 [8.36]) and sustained vowels (mean [SD] = 16.91 [11.08]). Ratings of dysphonia severity and speech clarity using 10-cm visual analog scales suggested mild-to-moderate dysphonia in connected speech (mean [SD] = 2.11 [1.72]) and sustained vowels (mean [SD] = 3.13 [2.20]) and mildly reduced speech clarity (mean [SD] = 1.46 [1.36]). Videolaryngostroboscopic ratings indicated mild-to-moderate dryness and mild reductions in overall laryngeal function. Voice Handicap Index scores indicated mild-to-moderate voice symptoms (mean [SD] = 43 [23]). Conclusion: Individuals with pSS may experience dysphonia and articulatory imprecision, typically in the mild-to-moderate range. These findings have implications for diagnostic and referral practices in pSS.